Umbilical cord mesenchymal stem cells for regenerative treatment of intervertebral disc degeneration - Huang, Huagui; Liu, Xin; Wang, Jinzuo; Suo, Moran; Zhang, Jing; Sun, Tianze; Zhang, Wentao; Li, Zhonghai (Frontiers in Cell and Developmental Biology, 2023)
Intervertebral disc degeneration is thought to be a major contributor to low back pain, the etiology of which is complex and not yet fully understood. To compensate for the lack of drug and surgical treatment, mesenchymal stem cells have been proposed for regenerative treatment of intervertebral discs in recent years, and encouraging results have been achieved in related trials. Mesenchymal stem cells can be derived from different parts of the body, among which mesenchymal stem cells isolated from the fetal umbilical cord have excellent performance in terms of difficulty of acquisition, differentiation potential, immunogenicity and ethical risk.